Dissemination of salt Tolerant wheat varieties through frontline demonstrations approach for sustainable wheat production in Pali district of Rajasthan - Meena, Moti Lal; Singh, Dheeraj (Journal of Cereal Research, 2025)
Front line demonstrations (FLDs) on wheat were laid down at 465 farmers’ fields to demonstrate production potential and economic benefits of improved production technologies comprising salinity tolerance varieties namely KRL 210, KRL 213, KRL 19 and KRL 1-4 in Pali district of arid zone of Rajasthan state during Rabi seasons from 2012-13 to 2017-18 in irrigated farming situation. The findings of the study revealed that the improved production technologies recorded an additional yield ranging from 7.1 to 16.0 q/ha with a mean of 11.1 q/ha. The per cent increase yield under improved production technologies ranged from 22.5 to 52.9 (KRL 210), 25.6 to 45.2 (KRL 213), 26.6 to 47.7 (KRL 19) and 33.8 to 45.5 (KRL 1-4) in respective years. The average extension gap, technology gap and technology index were 11.1q/ha, 11.3q/ha and 24.4 per cent, respectively in different salt tolerance varieties of wheat. The improved production technologies gave higher benefit cost ratio ranging from 2.0 to 3.0 with a mean of 2.4 as compared to local checks (1.8) being grown by farmers under locality. The results revealed that the maximum number of the respondents had medium level of knowledge and extent of adoption regarding recommended wheat production technology. The study reported lack of suitable salt tolerance HYV as major constraints by beneficiaries at rank first followed by low technical knowledge. Thus the productivity of wheat per unit area could be increased by adopting feasible scientific and sustainable management practices with a suitable salt tolerance variety. DOI.10.25174/2582-2675/2020/87064